PENERAPAN MODEL PEMBELAJARAN EVERONE IS TEACHER MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN SEJARAH SISWA KELAS XI SMAN 9 PEKANBARU - Yanti Ernita (JS (JURNAL SEKOLAH), 2019)
Abstract: The Implementation of Everone Is Teacher Learning Model Improves Student Learning Outcomes Historical Subjects for Class XI Senior High School 9 Pekanbaru. This study aims to improve the History of Learning Outcomes of the XI grade students of SMAN 9 Pekanbaru by applying the Everyone is teacher learning model. The subjects of this study were all students of class XI totaling 36 people. The form of research is classroom action research. The research instrument consisted of performance instruments and data collection instruments. Based on the results of the study, it was concluded that in the first cycle of students who completed reached 55.55% increased significantly by 97.22% in the second cycle, the value of students completeness has been reached. It shows that the learning outcomes of the students of Class XI Science 6 in SMAN 9 Pekanbaru can be improved through the Everyone is Teacher method.Keywords: Learning Model Everyone is Teacher, Learning Outcomes HistoryAbstrak: Penerapan Model Pembelajaran Everone Is Teacher Meningkatkan Hasil Belajar Peserta Didik Mata Pelajaran Sejarah Siswa Kelas XI SMAN 9 Pekanbaru. Penelitian ini bertujuan meningkatkan Hasil Belajar Sejarah siswa kelas XI SMAN 9 Pekanbaru dengan penerapan model pembelajaran Everyone is teacher. Subjek penelitian ini adalah semua siswa kelas XI berjumlah 36 orang. Bentuk penelitian adalah penelitian tindakan kelas. Instrumen penelitian ini terdiri dari instrumen unjuk kerja dan instrumen pengumpulan data. Berdasarkan hasil penelitian, diperoleh kesimpulan pada siklus I peserta didik yang tuntas mencapai 55,55% meningkat secara signifikan sebesar 97,22% pada siklus II, nilai ketuntasan siswa telah tercapai. Hal menunjukkan bahwa hasil belajar Sejarah siswa kelas XI IPA 6 di SMAN 9 Pekanbaru dapat ditingkatkan melalui metode Everyone is Teacher.Kata kunci: Model Pembelajaran Everyone is Teacher,  Hasil Belajar Sejarah